The technical side as a selection for footballers under 20 years - Boukechiche , Mawloud; Bengoua , Ali; Snouci , Abdelkrim; Bennama , Benaouda (sports creativity, 2025)
The study aimed to assess the skillful performance of football players according to scoring scales, which the research team considers more effective than unorganized transient observation, which leaves many errors leading to the loss of young talents in view from the selection of the best elements after their ranking according to qualifying qualifications become the parameter in many games and even World Championships have been approved by coaches and experts. This research was conducted on a sample of players from western Algeria aged under 20 years. The results resulted in a level difference between the players. The team was able to identify the best elements, which, in our opinion, represents the Algerian Football Regional Team